Physicians' Characteristics and Attitudes Towards Medically Assisted Dying for Non-Competent Patients with Dementia. Issue 1 (31st March 2022) - Bravo, Gina; Trottier, Lise; Arcand, Marcel
Abstract: The federal and Quebec governments are both considering extending medical aid/assistance in dying (MAID) to non-competent patients who would have requested MAID prior to losing capacity. In 2016–2017, we surveyed 136 Quebec physicians (response rate: 25.5%) on their attitudes towards extending MAID to such patients. Complementing our published findings, we herein identify demographic and practice characteristics that distinguish physicians who reported being open to extending MAID to non-competent patients with dementia, or willing to administer MAID themselves should it be legal, from those who were not. We found that physicians who were older, had stronger religious beliefs, were trained in palliative care, practiced in a teaching hospital, and had not received assisted dying requests in the year preceding the survey held less favourable attitudes towards MAID for non-competent patients with dementia. These findings will inform current deliberations as to whether assistance in dying should be extended to non-competent patients in some circumstances.